Endogenous Serotonin Acts on 5-HT(2C)-Like Receptors in Key Vocal Areas of the Brain Stem to Initiate Vocalizations in Xenopus laevis - Yu, Heather J. (American Physiological Society, 2010)
Serotonin initiates various rhythmic behaviors in vertebrates. Previously we have shown that serotonergic neurons innervate the central vocal pathway in the African clawed frog (Xenopus laevis). We also discovered that exogenous serotonin applied to isolated brains in vitro activates fictive vocalizations by activating 5-HT(2C)-like receptors. In this study, we examined the location of 5-HT(2C)-like receptors and determined whether endogenously released serotonin also initiates vocalizations by activating 5-HT(2C)-like receptors in male Xenopus brains. To this end, we first identified the specific location of 5-HT(2C)-like receptors using immunohistochemistry. We next examined which of the populations of neurons that express 5-HT(2C)-like receptors are functionally relevant for initiating fictive vocalizations by applying a 5-HT(2C) receptor agonist to brains transected at various levels. Of four populations of immunopositive neurons, we showed that 5-HT(2C)-like receptors located in two areas of the brain stem vocal circuit, the raphe nucleus and motor nucleus IX-X, initiate fictive vocalizations. We next showed that endogenous serotonin can also activate fictive vocalizations by increasing the extracellular concentration of endogenous serotonin using a selective serotonin reuptake inhibitor (SSRI). The SSRI-induced vocal initiation is also mediated by activation of 5-HT(2C)-like receptors because blockade of these receptors prevents fictive vocalization. The results suggest that in vivo release of serotonin initiates male vocalizations by activating 5-HT(2C)-like receptors in the brain stem vocal nuclei.